Mitigating Climate Change Towards Livable City (Case: Bandung City, West Java) - Ekawati, June; Sofari, Herdi; Rahmawati, Winda; Permata, Suci Indah; Setiawan, Edo (Journal of Architectural Design and Urbanism, 2023)
The increase in environmental problems due to climate change means that people in big cities need to carry out mitigation by reducing carbon emissions in their residential areas to make city areas more livable. This research aims to explore various problems and impacts of climate change in the city of Bandung as well as mitigation efforts carried out by the community to reduce carbon emissions while creating a livable city. The research method is qualitative-descriptive with primary data collection through interviews and field observations. The research was conducted in 4 urban village settlement locations, namely Cibunut Kampong in Kebon Pisang sub-district, Antapani Tengah sub-district, Neglasari sub-district, and Cisaranten Kidul sub-district, Bandung City. The research results showed that there are several spatial and environmental problems in the effort to achieve a livable Bandung City. The climate change mitigation efforts that have been implemented by the community in their residential areas while creating a more livable city area are by adding and managing green open space, independent waste management, managing Buruan sae (Urban farming) programs and vertical gardens, creating bio pores and absorption wells, maintaining environmental cleanliness and establishing collaboration with various related institutions